Contingent valuation: A pilot study for eliciting willingness to pay for a reduction in mortality from vaccine-preventable illnesses for children and adults in Bangladesh - Odihi, D; De Broucker, G; Hasan, Z; Ahmed, S; Constenla, D; Uddin, J; Patenaude, B (Elsevier, 2021)
Objectives The contingent valuation (CV) method elicits willingness to pay (WTP) for calculating the value of statistical life (VSL). CV approaches for assessing VSL are uncommon in many low and middle-income countries (LMICs). Between 2008 and 2018 only 44 articles utilized WTP in a health-related field and of these only 5 (11%) utilized CV to assess the WTP for a mortality risk reduction. We elicit WTP estimates and compute VSL using the CV method in Bangladesh. Methods The pilot study was primarily aimed at developing best practice guidelines for CV studies in LMICs to get more robust WTP estimates. To this end, we explored three methodological a) Varying the name of the intervention, keeping all other characteristics constant; b) varying the effectiveness of the health intervention and c) offering an overnight period to think about the WTP scenario. The survey was administered 413 randomly selected participants. VSL was for a 1/3000 mortality risk reduction. Results We had more males (54%) than females (46%) and the mean annual self-reported income was USD 5,683.36. Mean VSL is USD 11,339.70 with a median of USD 10,413. The ratio of child: adult WTP is approximately 1 by both gender and age category. The vaccine intervention had the largest amount of USD 0 WTP and protest responses (52% and 58% respectively). 93% of the participants were able to describe (teach-back) the vaccine effectiveness using their own family as an example. Conclusion Our study provides empirical evidence on how to better generate CV surveys to produce more robust WTP estimates.